The effects of rational and emotional sustainability appeals to consumers’ sensory perceptions and emotions - Abdullah, Muhammad; Ghazanfar, Sidra; Mukhtar, Sana; Ramzan, Muhammad (Frontiers in Sustainable Food Systems, 2025)
Extrinsic cues are widely used by researchers to develop consumers’ perceptions of food. This study aimed to investigate how consumer perceptions and emotional responses to roti prepared by replacing the proportion of wheat flour with wheat bran (an agriculture by-product) were affected by rational and emotional sustainability appeals. The experimental design included three evaluation sessions. Four different samples of roti were developed from four different bran-wheat proportions. Results showed that rational and emotional sustainability appeals affected the sensory perception of 10-90% and 20-80% of bran-wheat roti samples. However, sustainability appeal had no significant effect on the 30-70% bran-wheat roti sample. Results also show that responses under blind condition were associated with negative emotions, while responses under sustainability appeals were associated with positive emotions. Rational sustainability appeal was heavily associated with positive emotions as compared to emotional appeal. l.